EFFECTIVENESS OF ORGANIZATIONAL COMMUNICATIONS IN IMPROVING EMPLOYEE PERFORMANCE - Oktafien, Shinta; Santoso, Anton Budi (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to find out how much influence the effectiveness of organizational communication has on improving employee performance at PT. PLN (Persero) UP3 Garut. In this study, the population studied were all employees who worked at PT. PLN (Persero) UP3 Garut which amounted to 46 people and with the number of samples taken as much as the total population, so that the sampling technique used was saturated sampling technique. The research method used is descriptive and verification research methods and with data processing and analysis using simple linear regression analysis whose calculations use the help of SPSS version 25.0 software program. The results showed that the effectiveness of organizational communication can have a significant effect on improving employee performance at PT. PLN (Persero) UP3 Garut. This shows that the more effective the communication between superiors and subordinates or fellow employees at work, the better the work results shown by the employee.